(untitled) (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2025)
This study investigated the influence of flow behavior on the preparation of microsponges to enhance their stability for drug delivery applications. The viscosity of ethyl cellulose (EC) was modified by varying its concentration )3,4 and 5%wt) to evaluate its effect on the stability of the microsponges. Rheological properties were assessed using a cone-plate viscometer, generating viscosity, flow, and fitting curves to analyze ethyl cellulose behavior and its role in maintaining microsponges' integrity. Zeta potential measurements were conducted to evaluate colloidal stability while scanning electron microscopy (SEM) was used to examine the morphology of microsponges. The results indicated that the microsponge systems followed a power law model, exhibiting non-Newtonian shear-thining behavior, as evidenced by decreased viscosity with increasing shear rate. SEM analysis revealed a microsponge diameter ranging from 9.08 to 30.42 μm. Zeta potential values of (-36,-35, and -35) mV confirmed good stability. Overall, the findings revealed that increasing the viscosity of ethyl cellulose led to a slight decrease in microsponge stability. However, the stability remained within an acceptable range. Notably, the formulation (M1) exhibited the highest stability, with a zeta potential value of −36 mV, indicating superior dispersion stability. Therefore, M1 can be considered the optimum sample based on its balance between viscosity and stability.